Distortion and love : an anthropological reading of the art and life of Stanley Spencer - Rapport, Nigel, 1956- (Ashgate, 2016)
In this ground-breaking book, a theory of 'distortion' - of the way in which the processes of human life are subject to interference, diversion and transformation - is developed by way of the art of one of Britain's greatest twentieth-century painters and that art's public reception. Devoted to his native village of Cookham-on-Thames, Stanley Spencer painted not only landscapes and portraits with loving detail but also the 'memory-feelings' which he felt were a 'sacred' part of his consciousness. Yet Spencer was also a controversial public figure, with some taking the view that his visionary paintings were ugly distortions of human life, even marks of an immoral nature. Examining how Spencer lived his vision, how he painted it and wrote it, and also how his attempts to communicate that vision were received by his contemporaries and have continued to be interpreted since his death, the author posits distortion as key: an intrinsic aspect both of human creation and of human interaction. What we intend to make, to say, to do and have done, often mutates in the process of being expressed or put into effect: we live amid distortion. Love - the affective appreciation of one another - is then a means by which we accommodate distortion and its consequences in our lives. An illustration, through Stanley Spencer's story, of significant aspects of a human condition, this book will appeal across disciplines, including to art historians and students of Spencer's work, as well as to scholars of anthropology with interests in creativity, perception and interpretation.--Publisher.